2014
DOI: 10.5923/j.als.20140406.02
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Serum Granulocyte-Macrophage Colony-Stimulating Factor Levels among Diabetes Patients in Hilla City - Iraq

Abstract: Background: Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a pro-inflammatory cytokine with growth factor-like properties for monocytes and dendritic cells. Methods: Study subjects were recruited from the hospital in Hilla city. Healthy controls (n=15) and D.M. patients (n=35) were included in the study. Serum levels of GM-CSF and Anti-Insulin Antibody (AIA) measured by using ELISA technique. Results: The serum GM-CSF levels were significantly higher among diabetes subjects as compared with subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Previously, researchers reported that GM-CSF protects from diabetes by increasing a tolerogenic dendritic cells population [38]. Recently, Al-Hassnawi et al reported decreased GM-CSF levels in type 2 diabetes patients and found indirect association with blood glucose levels [39]. Present study also confirmed that GM-CSF could be used in the disease progressive marker for diabetes and diabetes with CAD.…”
Section: Discussionsupporting
confidence: 83%
“…Previously, researchers reported that GM-CSF protects from diabetes by increasing a tolerogenic dendritic cells population [38]. Recently, Al-Hassnawi et al reported decreased GM-CSF levels in type 2 diabetes patients and found indirect association with blood glucose levels [39]. Present study also confirmed that GM-CSF could be used in the disease progressive marker for diabetes and diabetes with CAD.…”
Section: Discussionsupporting
confidence: 83%
“…34 However, our results contrast to another study that G-CSF level decreased in patients with T1DM or T2DM compared to control. 35 G-CSF can play a significant role in stimulating vascular endothelium injury and granulocytes, which may play a significant role in the development of preeclampsia. 36 That effect could explain the significant positive correlation in the current study between the G-CSF and the endothelin-1 as the endothelin-1, known as a potent vasoconstrictor.…”
mentioning
confidence: 99%